Ion supplying material, and sealing composition

By forming a low-soluble salt layer on the surface of the structural material and filling cracks and voids with ion diffusion, the problems of moisture permeability and durability of underground structures are solved, and long-term water blocking and strength improvement are achieved.

JP2025020355APending Publication Date: 2025-02-12NAT UNIV CORP TOKAI NAT HIGHER EDUCATION & RES SYST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024196451
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-08-23
Filing Date
2024-11-11
Publication Date
2025-02-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent moisture penetration in underground structures in the long term and maintain the strength and durability of the structure, especially in high pore pressure environments.

Method used

By forming a surface layer containing an ion source on the surface of the structural material, low solubility salts (such as calcium carbonate) are used to form a surface layer containing an ion source, and the durability and strength of the structure are enhanced.

Benefits of technology

Effectively prevent moisture penetration, improve the long-term durability and strength of the structure, and maintain structural integrity even under high pore pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020355000001_ABST
    Figure 2025020355000001_ABST
Patent Text Reader

Abstract

To provide a technique for improving the strength or durability of a structure.SOLUTION: An ion supplying material includes an ion capable of forming calcium carbonate for filling voids or cracks in bed rock or in an earth-layer around a structural material, and the supplied ion diffuses into the voids or cracks present in the bedrock or the earth-layer around a structural material to form calcium carbonate with a counter ion present in the voids or cracks, to fill the voids or cracks therewith.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to ion supply materials and sealing compositions. [Background technology]

[0002] Many structures are being constructed not only on land, but also under the sea and underground. Some structures, such as tunnels and underground disposal sites for radioactive waste, need to be constructed at considerable depths underground. There are always gaps and cracks in the rock mass underground, through which groundwater springs out. The deeper the underground cavity to be excavated, the more difficult it becomes to avoid sudden springs due to an increase in the pore water pressure of the groundwater. Therefore, in order to safely utilize the underground environment and cavities for a long period of time, it is essential to have technology that can stop groundwater from leaking for a long period of time even under high pore water pressure. It is also necessary to improve the durability of the structural materials that make up the structures. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 4-1365 Summary of the Invention [Problem to be solved by the invention]

[0004] Conventionally, as described in Patent Document 1, for example, an injection tube was inserted into an injection hole formed in a crack, with its outlet facing the crack, and a crack injection agent such as a cement-based agent with good permeability was injected into the crack and allowed to harden inside the crack to stop water leaking.

[0005] In addition, when constructing underground structures such as tunnels, it is inevitable that gaps will occur at the contact points between underground structures such as tunnels and the ground (collectively referred to as "tunnel contact points") due to insufficient pouring of concrete on the top surface or the concrete shrinking as it hardens and dries. In this case, grout materials such as cement or mortar are filled into the tunnel contact points to prevent water leakage and reinforce them.

[0006] However, it has not been fully verified whether the watertightness of these conventional technologies and the durability of existing structures can be maintained for long periods of time, such as decades. There is a need to develop technologies that can maintain the strength and durability of watertight areas and structural materials over the long term.

[0007] The present disclosure has been made in view of such problems, and has an object to provide a technique for improving the strength or durability of a structure. [Means for solving the problem]

[0008] In order to solve the above problems, an ion supplying material according to one embodiment of the present disclosure contains ions capable of forming calcium carbonate for filling voids or cracks in the rock or stratum surrounding a structural material, and the supplied ions diffuse into the voids or cracks in the rock or stratum surrounding the structural material to form calcium carbonate with counter ions present in the voids or cracks, thereby filling the voids or cracks with calcium carbonate.

[0009] Another aspect of the present disclosure is a sealing composition comprising ions capable of forming calcium carbonate for filling voids or cracks in the rock or formation surrounding the structural material, and a source of ions for filling the voids or cracks with calcium carbonate by diffusing the provided ions into the voids or cracks in the rock or formation surrounding the structural material to form calcium carbonate with counter ions present in the voids or cracks. Effect of the Invention

[0010] According to the present disclosure, the strength or durability of a structure can be improved. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows a formation rate diagram for estimating the formation rate of concretions. [Diagram 2] FIG. 1 is a diagram illustrating an example of a structure according to an embodiment. [Diagram 3] FIG. 1 is a diagram illustrating an example of a structure according to an embodiment. [Figure 4] FIG. 1 is a diagram illustrating an example of a structure according to an embodiment. [Diagram 5] 1 shows the results of an experiment in which a poorly soluble salt is formed using a sample simulating a structural material according to an embodiment of the present invention. [Figure 6] This is a photograph of a thin section of a sample taken with a polarizing microscope (transmitted light) one week after the start of the experiment. [Figure 7] This is a photograph of a thin section of a sample taken with a polarizing microscope (polarized light) one week after the start of the experiment. [Figure 8] This is a photograph of a thin sample taken with a scanning electron microscope one week after the start of the experiment. [Figure 9] This is a photograph of a thin sample taken with a scanning electron microscope one week after the start of the experiment. [Figure 10] FIG. 1 shows the size distribution of calcium carbonate crystals formed in the samples one week after the start of the experiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present inventor is conducting research on spherical lumps called concretions that are found in sedimentary rock strata. These concretions are very dense and hard lumps of calcium carbonate (CaCO3) and often contain fossils inside. Concretions have been found in strata that are tens of thousands to tens of millions of years old, and in most cases, they remain spherical and unweathered even when the surrounding rocks and strata have been weathered due to exposure to the natural environment for many years. The fossils inside are also in extremely good condition, and it has been found that they have been preserved with almost no alteration for tens of millions of years.

[0013] According to the inventor's research, concretions are made up of carbon components that constituted the body tissues of fossilized organisms, and these carbon components are converted into bicarbonate ions (HCO3 - It was revealed that concretions are formed when carbon components that made up the organism's body leak out from the mouth or other places as bicarbonate ions, which then diffuse into the surrounding strata due to a concentration gradient, react with calcium ions present in the strata, and precipitate as calcium carbonate, which has low solubility in water. Due to this mechanism, concretions grow rapidly into spherical shapes around the organ where the carbon components that made up the organism's body leak out as bicarbonate ions, forming a chemically extremely stable and dense barrier around the organism in a short period of time that does not weather even when exposed to the natural environment, and thereafter preserving the fossils of the organisms inside in extremely good condition for tens of millions of years.

[0014] The inventors have considered that by applying this mechanism to form a surface layer of sparingly soluble salt such as calcium carbonate on the outer surface of a base material for forming a structure such as cement or concrete, it is possible to suppress deterioration of the structural material and dramatically improve the strength and durability of the structure.

[0015] That is, the structural material according to an embodiment of the present disclosure comprises a base material for forming a structure, and an ion supply source that supplies at least one of cations and anions that constitute a poorly soluble salt that is present inside or on the surface of the base material and has a solubility in water of a first value or less at the temperature of the environment in which the base material is disposed.

[0016] Since there are no concrete structures that have been built for more than several thousand years, no one knows whether concrete structures that have already been built will continue to last for a long time in the future. However, the existence of concretions proves that the surface layer formed by calcium carbonate has the durability to not deteriorate even when exposed to the natural environment for more than several thousand years. It is expected that by covering structural materials with a surface layer of calcium carbonate formed by the same mechanism as concretions, it will be possible to build structures that will last almost forever.

[0017] The sparingly soluble salt is, for example, calcium carbonate, and the ion source supplies, for example, calcium ions. In this case, the process is the opposite of that of concretion formation, but calcium ions supplied from the ion source diffuse into the surface and internal voids of the base material using the internal voids of the base material and the water present around it as a medium, and are converted into bicarbonate ions or carbonate ions (CO3 2- ) to precipitate calcium carbonate. As a result, the surface and internal voids of the structural material can be covered with a surface layer formed of poorly soluble salts such as calcium carbonate, similar to concretions, so that the structural material can be prevented from being chemically altered by moisture around the structural material or from substances such as acids, bases, oxidizing agents, and reducing agents dissolved in moisture penetrating into the structural material, from being deteriorated by environmental conditions such as temperature changes, and from being lost due to components constituting the base material leaching out to the outside, thereby improving the durability of the structural material. In addition, the surface of the structural material can be covered with a surface layer of a hard poorly soluble salt, and the internal voids of the structural material can be filled with the poorly soluble salt, so that the strength of the structural material can be improved. As in the process of concretions, bicarbonate ions may be supplied from an ion supply source, and a calcium carbonate precipitate may be generated by chemically reacting with calcium ions around the structural material.

[0018] The sparingly soluble salt may be any salt that has a sufficiently low solubility in water at the temperature of the environment in which the structural material is disposed, is chemically stable, and does not pollute the surrounding natural environment, and may be, for example, a carbonate such as calcium carbonate, magnesium carbonate, or iron (II) carbonate (siderite, siderite), a double salt such as calcium magnesium carbonate (CaMg(CO3)2, dolomite, dolomite), or a sulfate such as calcium sulfate. The solubility of calcium carbonate depends on the crystal structure, etc., but is approximately 0.0015 [g / 100 g water] at 20°C, the solubility of magnesium carbonate is 0.039 [g / 100 g water] at 20°C, the solubility of iron (II) carbonate is 0.00006554 [g / 100 g water] at 20°C, and the solubility of calcium sulfate is 0.24 [g / 100 g water] at 20°C. Therefore, the first value may be, for example, 0.3, more preferably 0.04, and even more preferably 0.002, as the solubility in 100 g of water at 20° C. The solubility of the poorly soluble salt may be lower than the solubility of the compound that is the main component of the base material. In other words, the first value may be the solubility value of the compound that is the main component of the base material described later, such as calcium hydroxide or calcium sulfate.

[0019] The poorly soluble salt may be appropriately selected depending on the environment in which the structural material is disposed. For example, calcium carbonate may be converted into calcium hydrogen carbonate, which has a relatively high solubility in water, by a chemical reaction with carbon dioxide, so when the structural material is disposed in an environment with a relatively high concentration of carbon dioxide, an ion source that supplies ions that form poorly soluble salts other than calcium carbonate may be contained in the structural material. In addition, calcium carbonate may be dissolved by a chemical reaction with acid, so when the structural material is disposed in an environment with a relatively low pH, an ion source that supplies ions such as iron (III) ions, whose hydroxides are poorly soluble in water, may be contained in the structural material. In this way, even if calcium carbonate on the surface, inside, or around the structural material is dissolved by an acid present around the structural material, the acid is neutralized by calcium carbonate, the pH is increased, and poorly soluble hydroxides are precipitated, so that the precipitated hydroxides can cover the surface of the structural material or fill voids inside or around the structural material. Ions for forming poorly soluble hydroxides may be, for example, iron (III) ions, aluminum ions, copper (II) ions, zinc ions, manganese ions, etc.

[0020] When the structural material is disposed underground or on the seabed, the ions supplied from the ion supply source diffuse from the surface of the structural material to the outside through the medium of groundwater that springs out from the strata or bedrock around the structural material, seawater around the structural material, etc. As a result, like concretions, the surface layer of sparingly soluble salts formed on the surface of the structural material grows toward the outside of the structural material and increases in thickness, thereby further improving the durability and strength of the structural material.

[0021] At this time, these ions also diffuse into voids and cracks in the rocks and strata surrounding the structural material, so that sparingly soluble salts are formed in the voids and cracks. This allows the cracks and voids in the rocks surrounding the structural material to be blocked with sparingly soluble salts, improving the strength of the rocks surrounding the structural material and preventing groundwater and seawater from seeping through cracks in the surrounding rocks from infiltrating into the structural material. Ions supplied from an ion supply source diffuse according to the concentration gradient of the ions, but since the concentration of the ions originally present around the structural material is usually low, the ions can be easily diffused to voids and cracks in the rocks surrounding the structural material without applying external force. In addition, since the ions diffuse in a state dissolved in water, the ions can be easily diffused into extremely minute voids and cracks at the atomic and molecular level regardless of the pore water pressure even deep underground, and sparing can be formed and blocked there, so that the surroundings of the structural material can be more reliably watertight. Such long-term reliable watertightness of groundwater infiltrating from the rocks was not possible with the above-mentioned conventional technology. In addition, since the amount of sparingly soluble salt that precipitates is determined by the concentration of cations and anions and the solubility product of the sparingly soluble salt, excessive amounts of sparingly soluble salt do not precipitate, which solves the problem in the conventional technology of filling voids with pressure, in which the pressure of an excessive amount of filler puts pressure on structural materials and the surrounding rock, which can cause cracks and destruction.

[0022] The amount and speed at which ions supplied from the ion supply source diffuse from the surface of the structural material to the outside are determined according to the diffusion coefficient of the ions around the structural material, the solubility in water of the poorly soluble salt at the temperature of the environment in which the structural material is disposed, the amount and supply speed of the ions supplied from the ion supply source, etc. Therefore, by appropriately selecting the amount and supply speed of the ions supplied from the ion supply source according to the diffusion coefficient of the ions around the structural material and the solubility in water of the poorly soluble salt at the temperature of the environment in which the structural material is disposed, it is possible to control the thickness of the surface layer formed on the surface of the structural material by the poorly soluble salt, the range of voids and cracks around the structural material blocked by the poorly soluble salt, etc.

[0023] Figure 1 shows a formation rate diagram for estimating the formation rate of concretions. This diagram is for estimating the formation rate of concretions from the width of the reaction edge of concretions formed from a creature called a horn shell, and the vertical axis shows the diffusion rate of bicarbonate ions, and the horizontal axis shows the reaction rate associated with the precipitation of calcium carbonate by reaction with calcium ions. If the diffusion rate of bicarbonate ions is too slow, a dense layer of calcium carbonate is formed early near the horn shell, and bicarbonate ions cannot diffuse any further outward, so the thickness of the reaction edge becomes thin. On the other hand, if the diffusion rate of bicarbonate ions is too fast, bicarbonate ions diffuse further outward before the concretions grow due to the precipitation of calcium carbonate, so the concretions can only grow to a certain thickness. Therefore, a surface layer of the desired thickness can be formed by supplying an appropriate amount of ions at an appropriate rate according to the diffusion coefficient of ions in the environment surrounding the structural material.

[0024] The thickness of the surface layer to be formed on the surface of the structural material may be determined according to the depth at which the structural material is disposed, the strength and components of the rock surrounding the structural material, the amount of groundwater surrounding the structural material, the components and amounts of chemical substances dissolved in the groundwater surrounding the structural material, etc. The type of ion supply source, the amount of ions that can be supplied, and the position and manner in which the ion supply source is disposed are designed so that ions are supplied in an amount and at a supply rate that will form a surface layer of the determined thickness.

[0025] The ion supply source may include an ion exchange resin to which the ions to be supplied are adsorbed. In this case, the ion exchange resin can be selected or designed to release the ions in an appropriate amount and supply rate depending on the type of ions to be supplied and the components, amounts, and pH of the chemical substances dissolved in the groundwater surrounding the structural material.

[0026] The ion supply source may include a capsule that contains and gradually releases the ions to be supplied. The ions contained in the capsule may be contained as a readily soluble salt having a solubility in water greater than a first value at the temperature of the environment in which the structural material is disposed, or may be contained as an ion exchange resin to which the ions are adsorbed. For example, in the case of an ion supply source that supplies calcium ions, the readily soluble salt may be calcium chloride (CaCl2) having a solubility in water of 74.5 [g / 100 g water] at 20°C, calcium nitrate (Ca(NO3)2) having a solubility in water of 121.2 [g / 100 g water], or calcium bicarbonate (Ca(HCO3)2) having a solubility in water of 16.6 [g / 100 g water] at 20°C. In this case, too, the material, thickness, shape, and the like of the capsule that releases ions at an appropriate amount and supply speed can be selected or designed according to the type of ions to be supplied and the components, amounts, and pH of the chemical substances dissolved in the groundwater surrounding the structural material. When the ion supply source includes a capsule, the capsule may be embedded inside the structural material. For example, it may be pre-mixed into cement or concrete, which is the base material of the structural material.

[0027] The ion supply source may include a sheet containing ions to be supplied. The ions contained in the sheet may be contained as an easily soluble salt having a solubility in water greater than a first value at the temperature of the environment in which the structural material is disposed, or may be contained as an ion exchange resin to which ions are adsorbed. In this case, too, the material, thickness, shape, etc. of the sheet can be selected or designed so as to release ions in an appropriate amount and supply rate depending on the type of ions to be supplied and the components, amount, pH, etc. of the chemical substances dissolved in the groundwater surrounding the structural material. When the ion supply source includes a sheet, the sheet may be attached to the surface of the structural material, or to the bedrock or stratum in which the structural material is disposed.

[0028] The ion supply source is disposed inside or around the structural material in an amount and distribution that releases ions in an appropriate amount and supply rate depending on the type of ions to be supplied and the components, amount, pH, etc. of chemical substances dissolved in the groundwater surrounding the structural material. In order to determine the type of ions to be supplied, when constructing a structure using the structural material, information is obtained on the composition of substances or minerals that currently exist or are expected to exist in the location where the base material is disposed or in the surrounding area. The ion supply source is provided in a type or amount that corresponds to the composition of substances or minerals that currently exist or are expected to exist in the location where the base material is disposed or in the surrounding area. For example, as described above, cations that form poorly soluble hydroxides may be supplied depending on the pH of the surrounding area. Also, a pH adjuster such as phosphoric acid may be contained. When the type of ions to be supplied are present in the surrounding area, it is not necessary to supply all of the amount of ions to be supplied from the ion supply source, so the amount of ions to be supplied may be reduced depending on the amount of ions present in the surrounding area. This makes it possible to reduce the cost of the structural material even when building a large-scale structure.

[0029] In a relatively short time after the structural material is installed, ions supplied from an ion supply source diffuse into the interior, surface, and exterior of the structural material using water as a medium, and a surface layer of sparingly soluble salt is formed on the surface of the structural material. The water that serves as the medium for ion diffusion is groundwater that springs up around the structural material when the structural material is installed underground, seawater or other water when the structural material is installed in water such as the sea, rainwater or moisture in the air when the structural material is installed outdoors, and moisture in the air when the structural material is installed indoors. Once a surface layer of sufficient thickness is formed on the surface of the structural material, the surface layer subsequently prevents moisture and the like from penetrating into the structural material, thereby preventing deterioration of the interior of the structural material.

[0030] Even if voids or cracks occur in the surface layer or inside the structural material due to external forces such as earthquakes, crustal movements, tides, and typhoons after the surface layer is formed, if ions supplied from the ion supply source contained in the structural material remain, the ions supplied from the ion supply source will diffuse into the voids and cracks in the surface layer or inside the structural material, and the voids and cracks can be filled or blocked by the poorly soluble salt precipitated by reacting with the counter ion. In this way, according to the technology of the present embodiment, a self-repair function can be imparted to the structural material, so that the durability of the structural material can be further improved. It is desirable to design the ion supply source so that ions supplied from the ion supply source remain even after the surface layer of the structural material is formed. In addition to an ion supply source designed to supply ions necessary for forming a surface layer on the surface of the structural material immediately after the structural material is disposed, an ion supply source containing soluble salts or ion exchange resins containing ions may be disposed near the surface layer in a container such as a capsule that breaks due to an external force that causes damage such as voids or cracks in the surface layer and releases its contents when the external force is applied to the structural material.

[0031] When the structural material is disposed in an environment where there are almost no counter ions for generating the poorly soluble salt, such as outdoors or indoors, a first ion supply source for supplying cations constituting the poorly soluble salt and a second ion supply source for supplying anions serving as counter ions may be contained in the structural material or disposed inside or around the structural material. In this case, the type of ion supply source, the amount of ions that can be supplied, and the position and manner of disposing the ion supply source are designed so that ions are supplied in an amount and at a supply rate that will form a surface layer of a desired thickness on the surface of the structural material. The positions, amounts, distributions, etc. of the first ion supply source and the second ion supply source may be designed so that the concentration of cations supplied from the first ion supply source and the concentration of anions supplied from the second ion supply source exceed the solubility product at the position where the surface layer is to be formed.

[0032] The base material of the structural material may include a sparingly soluble compound that is composed of the same type of cations or anions as those constituting the sparingly soluble salt and has a solubility in water of a second value or less that is greater than a first value at the temperature of the environment in which the structural material is disposed. In this case, the ion supply source is configured to be capable of supplying ions common to the sparingly soluble salt and the sparingly soluble compound. For example, the sparingly soluble salt and the sparingly soluble compound may be a sparingly soluble salt of calcium, and more specifically, the sparingly soluble salt may be calcium carbonate, and the sparingly soluble compound may be calcium hydroxide or calcium sulfate, which are main components of cement, concrete, and the like. As a result, even if groundwater, rainwater, or the like penetrates into the interior of a structural material such as concrete, the calcium ions supplied from the ion supply source can shift the dissolution equilibrium of the sparingly soluble compound in the structural material to the solid side, thereby suppressing the elution of calcium ions from the base material. As a result, the calcium ions that make up the base material are gradually lost through leaching to the outside, which prevents the formation of tiny voids and cracks inside the base material and thus reduces the strength of the structural material. This makes it possible to maintain the strength of the structural material for the long term, and ultimately to dramatically improve the durability of the structure.

[0033] The solubility of calcium hydroxide in water at 20°C is 0.173 [g / 100g water], and the solubility of calcium sulfate in water at 20°C is 0.24 [g / 100g water]. Therefore, the second value is, for example, 1, preferably 0.5, more preferably 0.25, and even more preferably 0.2. The solubility of the poorly soluble compound may be lower than the solubility of the readily soluble salt contained in the ion source. That is, the second value may be the solubility value of the readily soluble salt described above. The first value and the second value indicate the relationship between the solubility of the poorly soluble salt and the poorly soluble compound contained in one structural material. That is, the solubility of the poorly soluble salt formed by the ions supplied from the ion source contained in the structural material may be lower than the solubility of the poorly soluble compound contained in the base material of the structural material. For example, when gypsum containing calcium sulfate as a main component is used as the base material, calcium carbonate, which has a lower solubility than calcium sulfate, is selected as the sparingly soluble salt, whereas when a compound having a higher solubility than calcium sulfate is used as the base material, calcium sulfate may be selected as the sparingly soluble salt.

[0034] FIG. 2 is a schematic diagram showing an example of a structure according to an embodiment. By constructing an underground disposal site 50 for industrial waste, radioactive waste, etc. using the technology of the present disclosure, the outer wall of the underground disposal site 50 can be reliably blocked, and leakage of harmful substances, radioactivity, etc. from the underground disposal site 50 can be prevented for a long period of time. In addition, by constructing an underground structure such as a tunnel 60 using the technology of the present disclosure, the outer wall of the underground structure can be reliably blocked, and the voids in the tunnel contact portion between the underground structure and the ground can be filled, so that long-term water stopping is possible, and the strength and durability of the underground structure can be improved. Furthermore, by sealing the borehole 10 excavated when constructing the underground disposal site 50, the tunnel 60, etc. using the technology of the present disclosure, the blockage of the borehole 10 can be maintained for a long period of time.

[0035] FIG. 3 is a schematic diagram of an example of a structure according to an embodiment. The structure 40 shown in FIG. 3 is a structure for blocking a borehole 10 excavated underground, and includes a foundation 41 in contact with the ground and a rod-shaped body 42 in contact with the foundation 41. The foundation 41 and the body 42 are formed by the structural material 20 of the present disclosure. When constructing an underground facility such as an underground disposal site 50 or an underground structure such as a tunnel 60, a plurality of boreholes 10 are excavated to investigate the underground geology and the amount of groundwater. Conventionally, the borehole 10 has been blocked by pressing cement or the like into the borehole 10, but it is impossible to completely block it, and if many cracks and voids occur due to the deterioration of cement over time, they can become a path for the movement of groundwater and the like. When constructing a radioactive disposal site or the like underground, even a small void may leak radiation or radioactivity, so it is necessary to block the borehole 10 more reliably for a long period of time. If the borehole 10 is blocked by the structural material 20 of this embodiment, which includes a base material 21 such as cement and an ion source 22, the ions supplied from the ion source 22 diffuse into the fine cracks 12 and voids around the borehole 10 and react chemically with the counter ions present in the vicinity to form the sparingly soluble salt 30, so that the borehole 10 can be blocked more reliably. Even if the base material 21, such as cement, deteriorates over time and cracks or voids are formed, the ions supplied from the ion source 22 diffuse into the cracks or voids and react chemically with the counter ions to form the sparingly soluble salt, so that the cracks and voids can also be blocked, and the borehole 10 can be kept blocked for a long period of time.

[0036] Before the base material 21 such as cement is pressed in, a sheet-like ion source 22 may be attached to the wall surface of the borehole 10, and then the base material 21 such as cement may be pressed into the borehole 10. Before the base material 21 is pressed in, a liquid containing an ion exchange resin or a capsule-like ion source 22 may be injected into the borehole 10 to apply the ion source 22 to the wall surface of the borehole 10, and then the base material 21 such as cement may be pressed into the borehole 10. Before the base material 21 is pressed in, the ion exchange resin or the capsule-like ion source 22 may be mixed with the base material 21, and then the structural material 20 including the ion source 22 and the base material 21 may be pressed into the borehole 10. Silica, alumina, sand, crushed surrounding rocks, etc. may be further mixed into the base material 21 as a filler. This can reduce the cost of construction, and can protect the structural material and the sealing of the sparingly soluble salt from acids, etc., and improve durability.

[0037] FIG. 4 is a schematic diagram of an example of a structure according to an embodiment. The structure 40 shown in FIG. 4 is a structure constituting a wall surface separating a space 14 such as a cavity formed underground, a facility such as an underground disposal site 50, or a tunnel 60 from a surrounding bedrock 16, and includes a foundation 41 set on the ground so as to be in contact with the ground, and a tunnel-shaped skeleton 42 formed on the foundation 41 so as to be in contact with the foundation 41. The skeleton 42 includes a wall surface erected on the foundation 41, and a roof body installed on the wall surface. The foundation 41 and the skeleton 42 are formed of the structural material 20 of the present disclosure. In the example of FIG. 4, a sheet-shaped ion supply source 22 is attached to the outside of a wall surface formed of a base material 21 such as concrete. As a result, ions diffuse from the sheet of ion supply source 22 into the outer rock mass 16, and cracks 12 in the rock mass 16 and voids in the tunnel contact portion between the foundation 41 and the rock mass 16 can be blocked with the sparingly soluble salt 30, improving the strength of the rock mass 16 and suppressing the outflow of groundwater, etc. Also, ions diffuse from the sheet of ion supply source 22 into the inner base material 21, and a surface layer of sparingly soluble salt can be formed on the surface of the base material 21, improving the strength and durability of the structural material 20.

[0038] Before the base material 21 such as concrete is arranged on the wall surface, the sheet-like ion supply source 22 may be attached to the rock 16 around the space 14 such as a tunnel, and then the base material 21 may be arranged inside the sheet. Before the base material 21 is arranged, a liquid containing an ion exchange resin or a capsule-like ion supply source 22 may be applied or sprayed onto the rock 16 around the tunnel to form a coating of the ion supply source 22, and then the base material 21 may be arranged inside the coating. Before the base material 21 is arranged, the ion exchange resin or the capsule-like ion supply source 22 may be mixed with the base material 21, and then the structural material 20 containing the ion supply source 22 and the base material 21 may be arranged on the rock 16 around the tunnel. Silica, alumina, sand, crushed surrounding rocks, etc. may be further mixed into the base material 21 as a filler. This can reduce the cost of construction, and can protect the structural material and the sealing of the sparingly soluble salt from acids, etc., and improve durability.

[0039] The structure according to the embodiment may be a structure that is set underwater or outdoors. In this case, there is no stratum or bedrock outside the structural material, and water or air is present. When set in the sea, ions that can form a poorly soluble salt together with ions contained in seawater may be supplied from the ion supply source, but when set outdoors, there may be cases where a sufficient amount of ions to form a surface layer of poorly soluble salt is not contained in the air or rainwater. Even when the structure is set underground, the same applies when the amount of groundwater present in the surrounding area is small. In this case, as described above, a first ion supply source that supplies cations that constitute the poorly soluble salt and a second ion supply source that supplies anions may be provided. Both ion supply sources may be formed in a sheet shape and the two may be overlapped and attached to the surface of the structural material, or one of the ion supply sources may be formed in a sheet shape and the other ion supply source may be contained in the sheet in the form of a capsule or the like.

[0040] The structural material according to the embodiment may have a surface layer of a poorly soluble salt formed on the surface of the base material. In this case, the poorly soluble salt may be generated by ions supplied from an ion source contained in the structural material, or may be generated by applying or spraying a first liquid containing cations constituting the poorly soluble salt and a second liquid containing anions constituting the poorly soluble salt to the surface of the structural material or the surface of the rock or stratum on which the structural material is disposed. In the latter case, a structural material whose surface is protected by a surface layer of a poorly soluble salt can be manufactured by a simpler method, and a structure can be constructed by using a structural material whose surface is protected by a surface layer of a poorly soluble salt by a simpler construction method. In this case, the structural material may or may not contain an ion source. When the ion source is contained in the structural material, the strength of the structural material can be improved by filling voids and cracks inside the structural material with the poorly soluble salt, and the durability of the structural material can be improved by the self-repair function.

[0041] The sealing composition can be used to form a surface layer on the surface of a base material for forming the structure of the structural material according to the embodiment, or to fill or block voids or cracks inside or outside the base material. The sealing composition contains cations or anions capable of forming a poorly soluble salt having a solubility in water of a predetermined value or less at the temperature of the environment in which it is disposed, and an ion exchange resin to which the cations or anions are adsorbed. This sealing composition is used to form a structural material containing an ion supply source in the form of an ion exchange resin.

[0042] A sealing composition according to another embodiment includes a cation or anion capable of forming a poorly soluble salt having a solubility in water of a predetermined value or less at the temperature of the environment in which the composition is placed, and a counter ion capable of forming a readily soluble salt between the cation or anion and the counter ion having a solubility in water of a predetermined value or more at the temperature of the environment in which the composition is placed. This sealing composition is used to form a structural material containing an ion source in the form of a capsule or sheet, or to coat or spray the structural material to form a surface layer of the poorly soluble salt on the surface of the structural material.

[0043] A sealing composition according to yet another embodiment includes a sparingly soluble salt having a solubility in water of a predetermined value or less at the temperature of the environment in which the composition is disposed. The sealing composition is used to form a surface layer on the surface of a structural material and to seal the surface of the structural material.

[0044] An ion supplying material can be used to manufacture a structural material according to an embodiment. The ion supplying material supplies at least one of cations and anions constituting a poorly soluble salt whose solubility in water at the temperature of the environment in which the structural material is disposed is equal to or less than a predetermined value. The ion supplying material includes an ion exchange resin containing at least one of cations and anions constituting a poorly soluble salt, or a capsule containing a readily soluble salt or ion exchange resin containing one of cations and anions and whose solubility in water at the temperature of the environment in which the structural material is disposed is greater than a predetermined value, or a sheet containing a readily soluble salt or ion exchange resin. The ion supplying material is used to manufacture a structural material including an ion supply source in the form of an ion exchange resin, capsule, or sheet.

[0045] The technology of the present embodiment can also be applied to improve the strength and durability of an existing structure. By attaching a sheet of an ion source to the surface of a structural material constituting an existing structure or injecting a liquid containing an ion source into the inside of the structural material, it is possible to block voids and cracks present inside or around the structural material constituting the existing structure, and to impart a self-repairing function to the structural material constituting the existing structure, thereby improving the strength and durability of the structure. In addition, by applying or spraying a first liquid containing cations constituting a poorly soluble salt and a second liquid containing anions to the surface of the existing structure, a surface layer of poorly soluble salt is formed on the surface of the existing structure, thereby improving the strength and durability of the structure.

[0046] The technology of this embodiment can also be applied to bond structural materials together. By attaching a sheet of an ion supply source to the bonding surfaces of one or both structural materials, applying a liquid containing an ion supply source, or incorporating an ion supply source in advance inside one or both structural materials, and then bonding the bonding surfaces of the structural materials together, ions supplied from the ion supply source are diffused to the bonding surfaces, and the voids between the structural materials can be filled with the poorly soluble salt, so that the poorly soluble salt can bond a plurality of structural materials together in an airtight and liquidtight manner. An ion supply source may be injected into the bonding surfaces of the structural materials together. For example, by injecting an ion supply source into the bonding surfaces of structures constituting an existing structure, or into a tunnel contact portion between an underground structure such as an existing tunnel 60 and the ground, the adhesion of the bonding surfaces and the tunnel contact portion can be improved, and the strength and durability of the structure can be improved.

[0047] [Example] FIG. 5 shows the results of an experiment to form a poorly soluble salt using a sample simulating a structural material according to the embodiment. Approximately 1 g of agar and approximately 9 g of sodium bicarbonate (NaHCO3) were added to 100 g of water, heated to dissolve, and then cooled to solidify, to create a cubic sample with a size of approximately 1 cm on each side. The solubility of sodium bicarbonate is 9.6 g per 100 g of water at 20°C, so this sample contains an amount of sodium bicarbonate that is nearly saturated at room temperature. This sample was impregnated with an aqueous solution containing calcium ions at a concentration similar to that of groundwater, an aqueous solution containing calcium ions at a concentration similar to that of seawater, an aqueous solution containing calcium ions at a concentration 10 times that of seawater, an aqueous solution containing calcium ions at a concentration 100 times that of seawater, and an aqueous solution of calcium chloride as a control experiment, and the change in mass over time was measured. The results are shown in FIG. 5.

[0048] In all samples, the mass increased by several percent to several tens of percent within a few days from the start of the experiment, and remained constant after 10 days. In addition, all samples became cloudy overall within a few days from the start of the experiment and changed to a hard texture. From this result, it was confirmed that in all samples, calcium ions contained in the solution surrounding the sample diffused into the sample, calcium carbonate precipitates were formed within a few days from the start of the experiment, and thereafter, impregnation of the solution into the inside of the sample was suppressed, and the mass did not change. Since the formation of calcium carbonate precipitates was confirmed not only in aqueous solutions containing high concentrations of calcium ions, but also in aqueous solutions with concentrations similar to groundwater and seawater, it was confirmed that when the structural material of the embodiment is disposed in an environment where groundwater or seawater is present, calcium carbonate precipitates are generated in a short period of time, voids and cracks are filled, and a surface layer is formed.

[0049] Figures 6 and 7 are photographs of a thin slice of the sample taken with a polarizing microscope one week after the start of the experiment. The width of the image is about 0.5 mm. Figures 8 and 9 are photographs of a thin slice of the sample taken with a scanning electron microscope one week after the start of the experiment. The growth of aggregates of calcium carbonate crystals of several μm to several tens of μm was confirmed.

[0050] Figure 10 shows the size distribution of calcium carbonate crystals formed in the sample one week after the start of the experiment. The size of the calcium carbonate formed in the sample was very uniform, and in particular, crystal particles with diameters of 8 to 12 μm accounted for about 90% of the total. Such an occurrence, in which aggregates of calcium carbonate crystals with uniform particle sizes grow and form deep in the medium, is not seen in nature. In nature, there is always contamination with other substances such as sand and mud, and aggregates of only calcium carbonate crystals with uniform microscopic particle sizes do not exist. Furthermore, occurrences in which aggregates of only artificial calcium carbonate crystals are concentrated, for example, in the shape of a bunch of grapes, are not observed in nature.

[0051] The calcium carbonate crystals in the medium continue to grow over time, reaching several hundred micrometers in size after a few weeks. As the calcium carbonate crystals grow, the distribution density of the calcium carbonate crystals in the medium increases, and it has been confirmed that the mechanical strength of the medium also improves.

[0052] The present disclosure has been described above based on examples. These examples are merely illustrative, and it will be understood by those skilled in the art that various modifications are possible in the combination of each component and each treatment process, and that such modifications are also within the scope of the present disclosure.

[0053] In the embodiment, the surface layer is formed on the surface of the structural material by a sparingly soluble salt, but the surface layer may be formed on the surface of the structural material by a sparingly soluble compound other than salt. In this case, a compound that is easily soluble in water itself but reacts chemically with other compounds present in the environment in which the structural material is disposed to produce sparingly soluble precipitates may be supplied from a supply source disposed inside or around the structural material. For example, a supply source that supplies zinc ions may be disposed in a structural material that constitutes a structure constructed underground near a volcano, and a coating of zinc sulfide produced by reaction with hydrogen sulfide present in the surroundings may be formed on the surface of the structural material.

[0054] An overview of one embodiment of the present disclosure is as follows. A structural material according to one embodiment of the present disclosure includes a base material for forming a structure, and an ion supply source that supplies at least one of cations and anions constituting a poorly soluble salt that is present inside or on the surface of the base material and has a solubility in water of a first value or less at the temperature of the environment in which the base material is disposed. According to this embodiment, a surface layer of the poorly soluble salt can be formed on the surface of the base material by the ions supplied from the ion supply source, thereby improving the strength and durability of the structural material.

[0055] The ion supply source may include an ion exchange resin having at least one of cations and anions adsorbed thereon. According to this embodiment, the amount and speed of ion supply can be appropriately designed.

[0056] The ion supply source includes a capsule, the capsule encapsulating a readily soluble salt or an ion exchange resin, the readily soluble salt being a salt containing either a cation or an anion and having a solubility in water greater than a first value at the temperature of the environment in which the base material is disposed, and the ion exchange resin may contain at least one of a cation and an anion. According to this embodiment, the amount and speed of supply of ions can be appropriately designed.

[0057] The ion supply source includes a sheet, the sheet includes a readily soluble salt or an ion exchange resin, the readily soluble salt is a salt including either a cation or an anion, and has a solubility in water greater than a first value at the temperature of the environment in which the base material is disposed, and the ion exchange resin may include at least one of a cation and an anion. According to this embodiment, the amount and speed of supply of ions can be appropriately designed.

[0058] The first value may be a value of the solubility of a compound that is a main component of the base material. According to this embodiment, a surface layer of a sparingly soluble salt that is less soluble than the main component of the base material can be formed on the surface of the base material, thereby improving the strength and durability of the structural material.

[0059] The poorly soluble salt may be calcium carbonate. According to this embodiment, it is possible to improve the strength and durability of a structural material having concrete, cement, or the like as a base material.

[0060] The base material includes a poorly soluble compound whose solubility in water at the temperature of the environment in which the base material is disposed is equal to or less than a second value that is greater than a first value, and the poorly soluble compound may include at least one of the cations and anions that constitute the poorly soluble salt. According to this embodiment, it is possible to prevent the poorly soluble compound that constitutes the base material from dissolving out to the outside and reducing the strength of the structural material.

[0061] The poorly soluble salt and the poorly soluble compound may be a poorly soluble salt of calcium. The poorly soluble salt may be calcium carbonate, and the poorly soluble compound may be calcium hydroxide, calcium oxide, or calcium sulfate. According to this embodiment, it is possible to improve the strength and durability of a structural material having concrete, cement, or the like as a base material.

[0062] The voids inside the structural material may be filled with the sparingly soluble salt, which can improve the strength of the structural material.

[0063] A surface layer containing a sparingly soluble salt may be formed on the surface of the structural material or base material, which can improve the strength and durability of the structural material.

[0064] The ion source may be configured to supply an amount of cations or anions capable of forming a surface layer of a predetermined thickness on the surface of the structural material or base material, thereby improving the strength and durability of the structural material.

[0065] The ion source may be configured to supply an amount of cations or anions that is capable of forming a surface layer of a predetermined thickness on the surface of the structural material or base material according to the diffusion coefficient of the cations or anions around the structural material or base material. According to this aspect, the thickness of the surface layer formed on the surface of the structural material can be appropriately controlled according to the environment in which the structural material is disposed.

[0066] Cracks or voids occurring in the surface layer after the surface layer is formed may be self-repaired by the sparingly soluble salt. According to this embodiment, the strength and durability of the structural material can be improved.

[0067] Another aspect of the present disclosure is also a structural material. The structural material includes a base material for forming a structure, and a surface layer formed on the surface of the base material, the surface layer including a sparingly soluble salt having a solubility in water of a first value or less at the temperature of the environment in which the base material is disposed. According to this aspect, the strength and durability of the structural material can be improved.

[0068] The base material includes a poorly soluble compound whose solubility in water at the temperature of the environment in which the base material is disposed is equal to or less than a second value that is greater than a first value, and the poorly soluble compound may include at least one of the cations and anions that constitute the poorly soluble salt. According to this embodiment, it is possible to prevent the poorly soluble compound that constitutes the base material from dissolving out to the outside and reducing the strength of the structural material.

[0069] The poorly soluble compound may be calcium hydroxide, calcium oxide, or calcium sulfate. According to this embodiment, it is possible to improve the strength and durability of a structural material having concrete, cement, or the like as a base material.

[0070] Yet another aspect of the present disclosure is a structure. The structure includes a foundation and a skeleton in contact with the foundation, at least one of the foundation and the skeleton includes a structural material, the structural material includes a base material for forming the structure, and a sparingly soluble salt having a solubility in water of a predetermined value or less at the temperature of the environment in which the base material is disposed is formed on a surface of the base material or in a void inside or around the base material. According to this aspect, the strength and durability of the structure can be improved.

[0071] The structure may be a structure that blocks a cavity excavated underground. The structure may be a structure that constitutes a wall surface of a space formed underground. Voids or cracks in the ground around the structure may be blocked with the sparingly soluble salt. According to this aspect, the strength of the stratum or bedrock around the structure can be improved, and the strength and durability of the structure can be improved.

[0072] The structure may be a structure that is fixedly set underwater or outdoors. According to this aspect, the strength and durability of the structure can be improved.

[0073] Yet another aspect of the present disclosure is a method for constructing a structure using a structural material, the method comprising the steps of providing a base material and providing an ion source inside or on a surface of the base material. According to this aspect, the strength and durability of the structure can be improved.

[0074] The step of providing the ion supply source may include a step of incorporating the ion supply source in the base material prior to the step of disposing the base material. According to this aspect, the strength and durability of the structure can be improved by a simple construction method.

[0075] The structure is a structure that constitutes a wall surface of a space formed underground, and the step of providing the ion source may include a step of forming a layer including the ion source on the surface of the rock or stratum surrounding the space in which the base material is to be disposed, prior to the step of disposing the base material. According to this aspect, the strength and durability of the underground structure can be improved by a simple construction method.

[0076] The structure is a structure that constitutes a wall surface of a space formed underground, and the step of providing the ion source may include a step of injecting the ion source between the base material and the bedrock or stratum surrounding the space or into the inside of the structure material after the step of disposing the base material. According to this aspect, the strength and durability of the underground structure can be improved by a simple construction method.

[0077] The method for constructing a structure may further include a step of acquiring information on the composition of a substance or mineral that is currently present or expected to be present in the future at a location where the base material is disposed or in the vicinity thereof, and in the step of providing an ion source, the type or amount of the ion source may be provided according to the composition of the substance or mineral. According to this aspect, an appropriate type of sparingly soluble salt can be generated according to the environment surrounding the structure, thereby improving the strength and durability of the structure.

[0078] Yet another aspect of the present disclosure is a method for constructing a structure using the above-mentioned structural material, comprising the steps of disposing a base material and forming a surface layer containing a sparingly soluble salt on a surface of the base material. According to this aspect, the strength and durability of the structure can be improved.

[0079] The step of forming the surface layer may include a step of applying or spraying a first liquid containing cations constituting the poorly soluble salt and a second liquid containing anions constituting the poorly soluble salt to the surface of the disposed base material. According to this aspect, the strength and durability of the structure can be improved by a simple construction method.

[0080] The structure is a structure that constitutes a wall surface of a space formed underground, and the step of forming the surface layer may include a step of applying or spraying a first liquid containing cations constituting poorly soluble salts and a second liquid containing anions constituting poorly soluble salts to the surface of the rock or stratum surrounding the space in which the base material is to be disposed, prior to the step of disposing the base material. According to this aspect, the strength and durability of the underground structure can be improved by a simple construction method.

[0081] The method for constructing a structure may further include a step of acquiring information on the composition of a substance or mineral that is currently present or expected to be present in the future at or around the site where the base material is disposed, and in the step of forming the surface layer, a surface layer containing a type of sparingly soluble salt corresponding to the composition of the substance or mineral may be formed. According to this aspect, a surface layer containing an appropriate type of sparingly soluble salt can be formed according to the environment surrounding the structure, thereby improving the strength and durability of the structure.

[0082] Yet another aspect of the present disclosure is a sealing composition. This sealing composition is for forming a surface layer on the surface of a base material for forming a structure, or for filling or sealing voids or cracks inside or outside the base material, and includes a cation or anion capable of forming a poorly soluble salt having a solubility in water of a predetermined value or less at the temperature of the environment in which the composition is disposed, and an ion exchange resin having at least one of the cation and the anion adsorbed thereon. According to this aspect, the strength and durability of the structural material and the structure constructed from the structural material can be improved.

[0083] Yet another aspect of the present disclosure is a sealing composition. This sealing composition is for forming a surface layer on the surface of a base material for forming a structure, or for filling or sealing voids or cracks inside or outside the base material, and includes a cation or anion capable of forming a poorly soluble salt having a solubility in water of a predetermined value or less at the temperature of the environment in which the composition is disposed, and a counterion capable of forming a readily soluble salt having a solubility in water of a predetermined value or more at the temperature of the environment in which the composition is disposed between the cation or anion. According to this aspect, the strength and durability of the structural material and the structure constructed using the structural material can be improved.

[0084] Yet another aspect of the present disclosure is a sealing composition. The sealing composition is for forming a surface layer on the surface of a base material for forming a structure, or for filling or sealing voids or cracks inside or outside the base material, and contains a sparingly soluble salt whose solubility in water at the temperature of the environment in which the composition is disposed is equal to or less than a predetermined value. According to this aspect, the strength and durability of the structural material and the structure constructed using the structural material can be improved.

[0085] The poorly soluble salt may be calcium carbonate. According to this embodiment, a safe and inexpensive sealing composition can be provided.

[0086] Yet another aspect of the present disclosure is a method for using a sealing composition. This method uses a sealing composition containing a cation or anion capable of forming a poorly soluble salt having a solubility in water of a predetermined value or less at the temperature of the environment in which the composition is disposed, and a counterion capable of forming a readily soluble salt having a solubility in water of a predetermined value or more between the cation or anion and the counterion at the temperature of the environment in which the composition is disposed, to form a surface layer on the surface of a base material for forming a structure, or to fill or block voids or cracks inside or outside the base material. According to this aspect, the strength and durability of the structural material and the structure constructed from the structural material can be improved.

[0087] Yet another aspect of the present disclosure is a sealing composition. The sealing composition is for forming a surface layer on the surface of a base material for forming a structure, or for filling or sealing voids or cracks inside or outside the base material, and contains a sparingly soluble salt whose solubility in water at the temperature of the environment in which the composition is disposed is equal to or less than a predetermined value. According to this aspect, the strength and durability of the structural material and the structure constructed using the structural material can be improved.

[0088] Yet another aspect of the present disclosure is a method for using a sealing composition. In this method, a sealing composition containing a sparingly soluble salt whose solubility in water at the temperature of the environment in which it is disposed is used to form a surface layer on the surface of a base material for forming a structure, or to fill or block voids or cracks inside or outside the base material. According to this aspect, it is possible to improve the strength and durability of the structural material and the structure constructed from the structural material.

[0089] The poorly soluble salt may be calcium carbonate. According to this embodiment, a safe and inexpensive sealing composition can be provided.

[0090] Yet another aspect of the present disclosure is an ion supplying material. This ion supplying material supplies at least one of cations and anions constituting a poorly soluble salt whose solubility in water at the temperature of the environment in which it is placed is a predetermined value or less. This ion supplying material includes an ion exchange resin containing at least one of cations and anions constituting a poorly soluble salt, or a capsule containing a readily soluble salt or ion exchange resin containing one of cations and anions and whose solubility in water at the temperature of the environment in which it is placed is greater than a predetermined value, or a sheet containing a readily soluble salt or ion exchange resin. According to this aspect, it is possible to improve the strength and durability of a structural material and a structure constructed using the structural material. [Industrial Applicability]

[0091] The present disclosure is applicable to structures and methods of constructing structures. [Explanation of symbols]

[0092] 10 borehole, 12 crack, 14 space, 16 bedrock, 20 structural material, 21 parent material, 22 ion source, 30 sparingly soluble salt, 40 structure, 41 foundation, 42 framework.

Claims

1. An ion supplying material containing ions capable of forming calcium carbonate for filling voids or cracks in the rock or stratum surrounding a structural material, the supplied ions diffusing into voids or cracks in the rock or stratum surrounding said structural material to form calcium carbonate with counter ions present in said voids or cracks, thereby filling said voids or cracks with calcium carbonate.

2. The ions are gradually released. The ion supply material according to claim 1 .

3. Salts of the above ions that are readily soluble in water The ion supply material according to claim 1 or 2.

4. The ions include at least one of bicarbonate ions, carbonate ions, and calcium ions. The ion supply material according to any one of claims 1 to 3.

5. Providing a counter ion capable of forming calcium carbonate with the ion The ion supply material according to any one of claims 1 to 3.

6. The counter ion is slowly released The ion supply material according to claim 5 .

7. A sealing composition comprising ions capable of forming calcium carbonate for filling voids or cracks in rock or stratum surrounding a structural material, the composition comprising an ion source for filling the voids or cracks with calcium carbonate by diffusing the supplied ions into the voids or cracks in the rock or stratum surrounding the structural material and forming calcium carbonate with counter ions present in the voids or cracks.

Citation Information

Patent Citations

  • Water stopping work for underground concrete wall

    JP1989111916A

  • Production of high strength aluminum alloy fin material

    JP1993043999A

  • Method for inhibiting precipitation of efflorescence

    JP2005048497A

  • Grout solution and grout work using the same

    JP2006249294A

  • Method for repairing concrete

    JP2010001195A